The effect of the thermal aging on polycarbonate. (2021) - Redjala, Sonya; Azem, Said; Ait Hocine, Nourredine
Abstract: Polycarbonate (PC) is a widely used amorphous polymer. Among its many interesting properties, we can mention, among others, transparency, impact resistance and low density. However, long exposure to temperature changes its physicochemical, thermal and mechanical properties. The aim of this study is to reveal the effect of the time of exposure to temperature, in air, on the properties of the PC. Thus, maintaining this material at 80 °C causes damage as revealed by Fourier transform infrared spectroscopy (FTIR) and microstructural observations by scanning electron microscopy (SEM). The thermal analyzes also made it possible to observe modifications of the molecular chains as well as modifications of the mechanical properties confirmed by mechanical tests.